Characterization of titanium welded joints by the orbital gas tungsten arc welding process for aerospace application - Garcia, José A. Orlowski De (2010)
In this work, three welding programs for orbital gas tungsten arc welding (GTAW), previously developed, were used, using pulsed current and increasing speed (#A), constant current (#B) and pulsed current and decreasing current (#C). One of these should be used for the propulsion system of the Satellite CBERS (China - Brazil Earth Resources Satellite). Welded joints using tubes of commercially pure titanium were obtained with these procedures, which were characterized by means of mechanical and metallographic tests. The obtained results showed that the three welding procedures produce welded joints free of defects and with adequate shape. Although small differences on mechanical properties and on microstructure have been observed, the three welding programs attained compatible results with international standards used in the aerospace segment. The welding program #B, due to the reduced heat input used, was considered to obtain slightly advantage over the others.